Encountering Silencing: Forms of Oppression in Individuals, Families and Communities - Buchholz, Michael B. (Karnac Books, 2024)
While trauma has, rightfully, come to the centre of our attention, silencing, an equally important topic, has never been thoroughly studied. This book breaks that silencing and elaborates on various forms of this insidious process from different perspectives. It addresses the key question of how we can "hear" silencing and respond appropriately.